Answer :

A = , |A| = 1


Then, adj A =


A – 1 =


B = , |B| = – 10


Then, adj B =


B – 1 =


Also, A.B =


AB =


|AB| = 936 – 946 = – 10


Adj(AB) =


(AB) – 1 =


Now B – 1A – 1 =


=


=


Hence, (AB) – 1 = B – 1 A – 1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

If <span lang="ENMathematics - Board Papers

Using matrices soMathematics - Board Papers

<span lang="EN-USMathematics - Board Papers

Using properties Mathematics - Board Papers

Using matrices, sMathematics - Board Papers

If A is square maMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

The management coMathematics - Board Papers

If A is an invertMathematics - Board Papers

If <iMathematics - Board Papers